Best Practice for Marketing Heritage Site: Analysing the Medina National Museum in Saudi Arabia - Ali Alyusuf (Asian Journal of Media and Communication, 2019)
Heritage tourism provides direct benefits for regional economies and enhances economic development within the local communities. This study investigates the best practices of Medina National Museum in the Kingdom of Saudi Arabia by analysing the values of the site, tourist motivations, stakeholder’s collaboration, and promotion management of the site. Applying the interpretive social science paradigm, this study is based on secondary data, which means that the researcher has gathered data from other scholars. This study finds religious and socio-cultural values of the site that could be taken into account as important values for a heritage site. This study also finds that religious, educational and authentic are the most important tourist motivations to the site. It has also identified the related stakeholders in Saudi Arabia and Madinah region and concludes that bureaucracy prevents effective partnerships between the related stakeholders, including private and public sectors. Finally, based on the results, the study offers some suggestions and recommendations to increase the number of visitors to the Medina National Museum, including applying appropriate marketing strategy focusing to the targeted Muslim tourists, whether domestic or international tourists.Keywords: Medina National Museum; heritage tourism; destination value; marketing strategy; tourist motivation.